The influence of emotional intelligence while buffer effect on stress - Cruz, Catarina (2020)
Introduction The rise of new technologies and globalization leads tend to a people management valuing the skills of emotional intelligence (EI) expressed. This assumes a positive impact on people management, especially in health care. Objective The present study aimed to clarify the relationship of IE with the perceived stress (PS) in the